(untitled) (Revista Argentina de Cirugía, 2021)
Background: inguinal surgery in the elderly, presents a dilemma to the treating surgeon. The surgical risks are directly related to comorbidities, common in that age group. The surgeon should carefully weigh the pros and cons of each particular patient. Objective: the purpose of this paper is to evaluate hernia complications resulting from a conservative approach in patients older than 70 years of age. Materials and Methods: all the patients older than 69 years, harboring an inguinal hernia that was not surgically treated for any reason and with a ≥ 6 months follow-up were enrolled at the abdominal wall Department of the Hospital Privado de Comunidad (Mar del Plata) in the period from January 2008 to May 2010. They were assigned to 3 groups according to their clinical situation: 1) Asymptomatic or oligosymptomatic patients (Group 1); 2) Symptomatic high risk patients (Group 2); 3) Refusal to surgery (Group 3). Complications related to the hernia during follow up were analyzed. Results: 93 patients were enrolled. Median age was 81 years. 72 patients belonged to Group 1, 15 patients belonged to Group 2 and 6 patients to Group 3. During follow up (mean 31 months) 32.2% of patients developed new symptoms and 7.5% had incarceration. None of these patients required urgent surgery. Conclusions: the complication rate reported in patients older than 70 years of age with inguinal hernia was higher than that reported in the literature. Incarceration did not cause mortality in the study population.